2019
DOI: 10.5114/amsad.2019.85406
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in heart failure outpatients: levels, associated factors, and the impact on quality of life

Abstract: Introduction Heart failure (HF) patients experience various psychosocial issues and physical symptoms such as fatigue, which adversely affect their quality of life (QoL). The aim of the study was to assess levels of fatigue in HF outpatients and the associated factors, as well as to explore the correlation between fatigue and QoL. Material and methods One hundred and thirty patients were enrolled in the study. Data collection was performed by the completion of “Minnesot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
3
30
0
6
Order By: Relevance
“…In the field of lymphoedema treatment in female breast cancer survivors, there are several research works in which the benefits of exercise treatment in reducing lymphoedema have been collected [36][37][38][39]. In the studies of DiSipo et al [9] and Baumann et al [25] subjective improvements in the quality of life of the patients, anxiety (as occurs in other pathologies that alter the quality of life [40,41]), the decrease in lymphoedema (evaluated with volumetry) and, equally important, the non-appearance of adverse effects in the study population, are revealed. However, to date, there is no review that focuses on the importance of exercise work in preventing the onset of lymphoedema [9,25].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of lymphoedema treatment in female breast cancer survivors, there are several research works in which the benefits of exercise treatment in reducing lymphoedema have been collected [36][37][38][39]. In the studies of DiSipo et al [9] and Baumann et al [25] subjective improvements in the quality of life of the patients, anxiety (as occurs in other pathologies that alter the quality of life [40,41]), the decrease in lymphoedema (evaluated with volumetry) and, equally important, the non-appearance of adverse effects in the study population, are revealed. However, to date, there is no review that focuses on the importance of exercise work in preventing the onset of lymphoedema [9,25].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 has demonstrated extensive bioactivity in immunomodulation, tumorigenesis, hematopoiesis, and inflammation [33][34][35], while TNF-α plays a possible role in B cell chronic lymphocytic leukemia [36][37][38]. The diagnostic values of these proinflammatory factors [39] in pediatric acute lymphoblastic leukemia have been proven in previous studies [40], and their expression in the serum of patients with P r e p r i n t leukemia often increases abnormally.…”
Section: Discussionmentioning
confidence: 99%
“…This non-specific, invisible and subjective symptom is characterized as a vicious circle since its consequences further exaggerate this experience [38,43,44]. Hopefully, understanding factors associated with fatigue will enhance individualized care and implementation of appropriate strategies [45,46]. A recent study on HF outpatients showed that fatigue was asso-ciated with NYHA stage, confidence to acknowledge health deterioration, decrease in appetite, dyspnea at night, edema in lower limbs, relations with health professionals, limitations in daily or social activities and financial worries [47].…”
Section: Discussionmentioning
confidence: 99%